2016
DOI: 10.3390/molecules21111600
|View full text |Cite
|
Sign up to set email alerts
|

1-Deoxynojirimycin: Occurrence, Extraction, Chemistry, Oral Pharmacokinetics, Biological Activities and In Silico Target Fishing

Abstract: 1-Deoxynojirimycin (DNJ, C 6 H 13 NO 4 , 163.17 g/mol), an alkaloid azasugar or iminosugar, is a biologically active natural compound that exists in mulberry leaves and Commelina communis (dayflower) as well as from several bacterial strains such as Bacillus and Streptomyces species. Deoxynojirimycin possesses antihyperglycemic, anti-obesity, and antiviral features. Therefore, the aim of this detailed review article is to summarize the existing knowledge on occurrence, extraction, purification, determination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 85 publications
0
40
0
1
Order By: Relevance
“…Some alkaloids in mulberry leaf are effective inhibitors of digestive enzymes in mammals. [ 19 ] These alkaloids, and especially 1-deoxynojirimycin (DNJ), [ 20 ] can reduce the activity of α-glucosidase by competitively inhibiting the binding of natural substrates to the active site of the enzyme. [ 21 ] In addition, DNJ has been reported to inhibit intestinal glucose absorption and accelerate hepatic glucose metabolism by directly regulating the expressions of several proteins involved in glucose transport, glycolysis, and gluconeogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Some alkaloids in mulberry leaf are effective inhibitors of digestive enzymes in mammals. [ 19 ] These alkaloids, and especially 1-deoxynojirimycin (DNJ), [ 20 ] can reduce the activity of α-glucosidase by competitively inhibiting the binding of natural substrates to the active site of the enzyme. [ 21 ] In addition, DNJ has been reported to inhibit intestinal glucose absorption and accelerate hepatic glucose metabolism by directly regulating the expressions of several proteins involved in glucose transport, glycolysis, and gluconeogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Prichard et al [ 21 ] reviewed several iminosugar derivatives with reported activities including glycosidase inhibition, and immunosuppressant, antibacterial, antiviral and anti-inflammatory effects. The iminosugar found in mulberry, DNJ, has garnered interest for antihyperglycemic, anti-obesity, and anti-viral biological activities [ 9 ]. The biological activities of iminosugar does not indicate potential for toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Iminosugars are polyhydroxylated alkaloids that mimic the structures of monosaccharides (N. [ 7 , 8 ]). In the iminosugar, a nitrogen atom replaces the oxygen atom in the ring of the chemical structure of these molecules [ 9 ]. An example of D-glucose and its equivalent iminosugar is shown below in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In their simplest structure, they typically mimic the corresponding furanose or pyranose monosaccharide skeleton by replacement of endocyclic oxygen with an amino function, resembling carbohydrate substrates or saccharide hydrolysis transition states ( Figure 2) [5][6][7]. After the isolation from bacteria (Streptomyces) of the first natural iminosugar, nojirimycin (NJ, 1) [2], the chemical synthesis and isolation from mulberry of deoxynojirimycin (DNJ, 2) [3], a potent α-and β-glucosidase inhibitor [4], opened the way to the advent of this new class of glycomimetics. In their simplest structure, they typically mimic the corresponding furanose or pyranose monosaccharide skeleton by replacement of endocyclic oxygen with an amino function, resembling carbohydrate substrates or saccharide hydrolysis transition states ( Figure 2) [5][6][7].…”
Section: Iminosugars: Powerful Glycomimeticsmentioning
confidence: 99%